Biological Tools to Deal with Pollution : Selected Advances and Novel Perspectives - Abdelaziz Ghanemi; Besma Boubertakh (Intelektual Pustaka Media Utama, 2014)
Pollution represents a problem common to economy and public health. Indeed, the public health, because of the divers’ type of pollutions, is facing divers challenges for which urgent solutions are required.The biology provides approaches not only to deal with the pollution, but also to obtain economic benefits. Some living organisms have particular metabolisms that allow them to assimilate and metabolite the polluting agents and thus reduce the impact they have on both environment and public health. On the other hand, the metabolic properties of specific organisms make the polluting elements raw materials to synthesize other elements that are benefits for economy and non-toxic for the ecology and the biohealth. Yet, other options such as the regulations and laws are required to improve the efficiency of these approaches.